Advancements in photovoltaic efficiency: The role of fluorine-doped CZTS in homojunction solar cells - Milad Yousefizad; Zohreh Golshan Bafghi; Amirmohammad Shahriyari; Andia Javanmardi; Naser Hakimi Raad; Ashraf Ahmadi Shadmehri; Siavosh Samoodi; Negin Manavizadeh; Ali Moafi (Heliyon)
Copper Zinc Tin Sulfide (CZTS) solar cells have absorbed significant appeal as an efficient approach for sustainable photovoltaic technology. This research introduces a groundbreaking approach to thin-film solar cells using a novel Fluorine-doped CZTS composition with a new device configuration. The DFT calculations indicate that F atoms prefer Cu sites and maintain a direct band gap in CZTS, promoting n-type conductivity. Optical studies demonstrate that F-doping enhances conductivity, refractive index, and light absorption through the visible spectrum. Furthermore, the performance of CZTS-based cells in both heterojunction and homojunction configurations is under investigation. The homojunction configuration with Al:ZnO intermediate layer enhances VOC and JSC compared to conventional heterojunction structures. The JSC and VOC of homojunction solar cells with AZO layer are 24.74 mAcm−2 and 0.94 V, respectively. The efficiency of the solar cell is optimized considering the thickness of the p-CZTS layer, which saturates at 21.8 % beyond 5 μm thickness. At the beginning of near-infrared wavelengths, the homojunction structure effectively absorbs light. Combining F-doped CZTS and homojunction configuration with a ZnO and AZO intermediate layer demonstrates superior performance due to reduced carrier recombination and enhanced photogeneration. The novel homojunction design advances CZTS-based technology, achieving impressive effectiveness using environmentally friendly materials.